2008
DOI: 10.1007/s11095-008-9609-0
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Modeling of the Blood–Brain Barrier Permeability for Diverse Organic Compounds

Abstract: Models developed in these studies can be used to estimate the BBB permeability of drug candidates at early stages of drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
125
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 67 publications
9
125
0
1
Order By: Relevance
“…QSAR modeling has also been helpful in predicting drug distribution/penetration into specific biological compartments such as the blood-brain barrier (BBB); for instance, a highly predictive model of penetration (R 2 = 0.80 in an external validation set of 10 compounds) as well as specific contributors to penetration, such as van der Waals surface area and active transport, was reported recently. 11 A similarly predictive model for FGT penetration would help inform the development process and assist in the search for ideal PrEP candidates.…”
mentioning
confidence: 99%
“…QSAR modeling has also been helpful in predicting drug distribution/penetration into specific biological compartments such as the blood-brain barrier (BBB); for instance, a highly predictive model of penetration (R 2 = 0.80 in an external validation set of 10 compounds) as well as specific contributors to penetration, such as van der Waals surface area and active transport, was reported recently. 11 A similarly predictive model for FGT penetration would help inform the development process and assist in the search for ideal PrEP candidates.…”
mentioning
confidence: 99%
“…Nevertheless, the model presented in this study is comparable or better than other published 2D-QSAR BBB models and show similar descriptors used by other authors. (Norinder et al, 2002;Katritzky et al, 2006;van Damme et al, 2008;Iyer et al, 2002;Konovalov et al, 2007;Subramanian et al, 2003;Zhao et al, 2007;Zhang et al, 2008;Narayanan et al, 2005;Young et al, 1988;Abraham, 2004;Goodwin et al, 2005). These findings can help future decisions about which groups are favorable or otherwise for CNS entry by BBB permeation, based on the physicochemical properties evaluated here.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, computerassisted drug design methodologies (CADD), such as quantitative structure-property and/or structure-activity relationship studies (QSPR and QSAR, respectively), may help to estimate biological data, reducing synthetic steps, predicting pharmacokinetic and pharmacodynamic profiles, constituting an important tool in the design and development of new drugs and novel leads (Katritzky et al, 2006). A literature review reported several studies, carried out on a number of different chemical structures, and in which 2D and 3D QSPR models have been proposed to predict logBB values (Katritzky et al, 2006;Van Damme et al, 2008;Iyer et al, 2002;Konovalov et al, 2007;Subramanian et al, 2003;Zhao et al, 2007;Zhang et al, 2008;Narayanan et al, 2005). Some of these models show a correlation between logBB and some physicochemical parameters, such as molecular refractivity (MR), molecular volume (V), acid ionization constant (K a and pK a ), thermodynamic parameters (solvation energy, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid such unjustified exploration of activity predictions, we used the concept of applicability domain. 41 …”
Section: Güner-henry Scoring Methodsmentioning
confidence: 99%